2006
DOI: 10.1007/s11524-006-9125-7
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Smoking Among Urban-Dwelling Canadian Men Who Have Sex with Men

Abstract: A small but consistent literature from the United States suggests increased risk for smoking among lesbians and men who have sex with men (MSM). Few studies have investigated smoking among MSM in other countries where different social norms and restrictions on smoking in public apply. We measured smoking behaviours in a convenience sample of urban-dwelling young Canadian MSM (median age 28 years). We compared the prevalence of smoking among MSM with that among other men in British Columbia (BC) using National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Several studies found associations between demographic correlates of smoking that are similar to characteristics identified in the general population, including younger age30 64 65 and lower educational attainment 8 14 21 31 65–67. Other common correlates with smoking were alcohol use14 31 65 68 and depression/depressive symptoms 30 65 69.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies found associations between demographic correlates of smoking that are similar to characteristics identified in the general population, including younger age30 64 65 and lower educational attainment 8 14 21 31 65–67. Other common correlates with smoking were alcohol use14 31 65 68 and depression/depressive symptoms 30 65 69.…”
Section: Resultsmentioning
confidence: 74%
“…These inequalities appear to exist internationally, albeit with limited research, with studies from around the world, including Australia,25 Mexico,26 Switzerland,27 Taiwan,28 Canada,29 30 and China 31. Some Irish32 and Canadian33 studies, however, show no evidence of an inequality in smoking prevalence, suggesting the need for confirmatory studies and additional efforts to identify the causes of health equality.…”
Section: Introductionmentioning
confidence: 99%
“…Higher smoking prevalence was found among Chinese MSM (66%) versus MSM in North America (34%-55%; Greenwood et al, 2005;Lampinen et al, 2006) and versus the general urban male population in China (56%; S. Lee et al, 2009). The 10% higher rate among Chinese MSM versus non-MSM may reflect a ceiling effect since smoking rates among Chinese men are quite high.…”
Section: Discussionmentioning
confidence: 89%
“…High smoking rates have been documented among MSM in North America (Austin et al, 2004;D'Augelli, 2004;Greenwood et al, 2005;Lampinen, Bonner, Rusch, & Hogg, 2006;McKirnan, Tolou-Shams, Turner, Dyslin, & Hope, 2006;Tang et al, 2004), but extremely limited research has examined smoking among MSM in developing countries. Given that different cultural factors may influence smoking, research must examine prevalence and correlates of smoking among MSM more globally.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking prevalence in China is high (Yang, 2008); roughly, 56% of men and 6% of women are current smokers (Lee et al, 2009). Men who have sex with men (MSM) are at high risk for smoking (Greenwood et al, 2005;Lampinen, Bonner, Rusch, & Hogg, 2006;McKirnan, Tolou-Shams, Turner, Dyslin, & Hope, 2006;Tang et al, 2004), but limited research has examined smoking among MSM in developing countries. One study of MSM in Shanghai, China documented a 66% smoking prevalence (Berg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%